Antifungal stewardship with an emphasis on candidaemia. (December 2019) - Capoor, Malini R.; Subudhi, Chinari P.; Collier, Andrew; Bal, Abhijit M.
Highlights: Antifungal stewardship needs attention due to emergence of multidrug resistant fungi. Implementation of antifungal stewardship involves understanding of opportunities and challenges. New ECMM guidelines on candidaemia facilitate antifungal stewardship. Abstract: Antimicrobial resistance is a global threat. To counter the growing menace of antibiotic resistance, several stewardship initiatives have been incorporated as part of the overarching strategy of healthcare delivery. In contrast, antifungal stewardship (AFS) has attracted less attention for several reasons, such as limited antifungal resistance and the lesser burden of fungal infections compared with bacterial infections. However, the emergence of resistant fungi, such as multidrug-resistant Candida auris, has provided impetus to AFS programmes. This review summarises existing data on AFS programmes, particularly in relation to invasive candidiasis, both in the empirical setting and in the setting of proven infection.